2018
DOI: 10.1186/s12967-018-1500-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of HIV Tat protein in HIV-related cardiovascular diseases

Abstract: The human immunodeficiency virus (HIV) is a major global public health issue. HIV-related cardiovascular disease remains a leading cause of morbidity and mortality in HIV positive patients. HIV Tat is a regulatory protein encoded by tat gene of HIV-1, which not only promotes the transcription of HIV, but it is also involved in the pathogenesis of HIV-related complications. This review is aimed at summarizing the current understanding of Tat in HIV-related cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 71 publications
0
11
1
1
Order By: Relevance
“…The regulatory Tat protein not only facilitates the transcription of HIV, but it is also implicated in the pathogenesis of endothelial dysfunction and atherosclerosis-associated CV complications in PLWH [51]. In contrast to our results supporting indirect effects of Tat on endothelial function mediated via leptin reduction, others have reported that HIV protein Tat stimulates oxidative stress by increasing ROS production and decreasing antioxidant capacity [52][53][54][55].…”
Section: Discussioncontrasting
confidence: 81%
“…The regulatory Tat protein not only facilitates the transcription of HIV, but it is also implicated in the pathogenesis of endothelial dysfunction and atherosclerosis-associated CV complications in PLWH [51]. In contrast to our results supporting indirect effects of Tat on endothelial function mediated via leptin reduction, others have reported that HIV protein Tat stimulates oxidative stress by increasing ROS production and decreasing antioxidant capacity [52][53][54][55].…”
Section: Discussioncontrasting
confidence: 81%
“…Changes in the adaptive immune system and persistent inflammation leading to severe ventricular electrophysiological remodeling could be the possible mechanisms. Indeed, experimental evidence, especially transgenic mouse models, provide a view of the pathophysiological mechanisms of HIV-related arrhythmia and strongly support the role for inflammation and pro-inflammatory cytokines (tumor necrosis factor-alpha [TNFα] and interleukin [IL]-1β) on cardiac potassium and calcium ion channels and associated pathologic electrical remodeling [18][19][20][21]. IL-1β decreases the calcium currents, whereas TNFα reduces potassium and sodium currents without affecting calcium currents.…”
Section: Discussionmentioning
confidence: 99%
“…Urbinati and co-workers in 2012 found that immobilized Tat induces actin cytoskeleton organization, formation of a v b 3 integrin(+)focal adhesion plaques, and recruitment of vascular endothelial growth factor receptor-2 (VEGFR2) in the ventral plasma membrane of adherent endothelial cells (96). Tat binding to the endothelial cells may also directly contribute to atherosclerosis and cardiovascular disease in patients with HIV (97).…”
Section: Endothelial Cells and Hiv-1 Protein Interactionsmentioning
confidence: 99%